A Novel Prediction Tool Based on Large Cohorts to Determine the Cancer-Specific Survival Probability of Patients With Locally Advanced Pancreatic Cancer After Irreversible Electroporation Treatment - He, Chaobin; Huang, Xin; Zhang, Yu; Lin, Xiaojun; Li, Shengping (Frontiers in Oncology, 2020)
Irreversible electroporation (IRE) is a novel method which was especially suitable for the treatment of locally advanced pancreatic cancer (LAPC). The purpose of this study was to evaluate probabilities of overall survival (OS) and cancer-specific survival (CSS) in patients with LAPC after IRE treatment and to construct nomograms to predict survival for these patients. Data of patients were retrospectively collected from the Surveillance, Epidemiology, and End Results (SEER) database and medical records of Sun Yat-sen University Cancer Center (SYSUCC). A total of 312 LAPC patients after IRE treatment were included into this study. The 3-year cumulative incidence of cancer-specific mortality for patients with LAPC after IRE treatment was 74.3%. Nomograms for predicting probabilities of OS, CSS and non-cancer-specific survival (NCSS) were built and calibrated with concordance index (C-index) and the area under receiver operating characteristic (ROC) curve (AUC). The established nomograms were well calibrated, with C-indexes of 0.782 for OS prediction, 0.729 for CSS prediction and 0.730 for NCSS prediction. Compared with TNM stage system, the established nomograms displayed higher values of AUC and showed better discriminatory power for predicting OS, CSS and NCSS. These nomograms were well calibrated and could serve to guide management of LAPC patients after IRE treatment.